2009
DOI: 10.1021/ma802372m
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Adducted Cation in the Release of Nitroxide End Group of Controlled Polymer in Mass Spectrometry

Abstract: The role of cations in the fragmentation of polymer nitroxide labile end groups, as often deplored in matrix-assisted laser desorption/ionization, was investigated. A combination of different spectroscopic techniques and theoretical calculations was implemented to address the mechanistic aspect of the end-group cleavage in a nitroxide-terminated poly(ethylene oxide) macroinitiator agent upon activation in mass spectrometry. When occurring during the ionization process, the homolytic cleavage of a C-ON bond in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…This increase in NO-C BDE strengthens the argument for Scheme 4 which favours the heterolytic NO-C and homolytic N-OC bond cleavage pathways in the event of nitroxide protonation. [31] Several prominent product ions in Fig. 5, including m/z 496 from HALS (5) and m/z 576 from HALS (6) are consistent in mass with the loss of both ether moieties from these bifunctional species.…”
Section: Esi-ms/ms Spectra Of Hals (5 and 6) (N-y Where Y = Oc 8 H 17mentioning
confidence: 72%
“…This increase in NO-C BDE strengthens the argument for Scheme 4 which favours the heterolytic NO-C and homolytic N-OC bond cleavage pathways in the event of nitroxide protonation. [31] Several prominent product ions in Fig. 5, including m/z 496 from HALS (5) and m/z 576 from HALS (6) are consistent in mass with the loss of both ether moieties from these bifunctional species.…”
Section: Esi-ms/ms Spectra Of Hals (5 and 6) (N-y Where Y = Oc 8 H 17mentioning
confidence: 72%
“…73 Mazarin et al later used quantum chemical calculations in addition to NMR-measurements to rationalize the observed fragmentation reactions of nitroxide functional PEOs with different adducted cations. 74 This interesting study showed that an advanced theoretical understanding of the complex ionization and dissociation processes of synthetic polymers can help in tuning and interpreting the structural information obtained in (co)polymer analysis by MS/MS. The prediction of polymer fragmentation patterns based (partially) upon quantum chemical calculations and computational modelling studies may be of increasing value in the future.…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…In the case of synthetic polymers prepared by nitroxide-mediated polymerization, protonation of the nitrogen atom of the nitroxide termination was demonstrated to induce an increase of the dissociation energy of the C−ON bond between the nitroxide end-group and the last monomer, hence preventing its spontaneous cleavage. 24 Accordingly, the y 2 •+ product ion would be generated only from precursor ions holding the proton on the nitroxide nitrogen in the second T moiety, whereas formation of the c 2…”
Section: ■ Introductionmentioning
confidence: 99%